Phenolic-storing cells: keys to programmed cell death and periderm formation in wilt disease resistance and in general defence responses in plants? - Beckman, C.H.
Specialized cells of plants synthesize phenolics and store them in their vacuoles during the normal processes of di_erentiation. Such phenolic-storing cells are distributed within most tissues. In some tissues they occur uniformly in all of the cells, whereas in other tissues they occur randomly scattered, and in still others they appear to be strategically located at potential points of entry. Based on the evidence presented herein, it is proposed that these cells can, Rrst, by decompartmentation, rapid oxidation of their phenolic content, and the ensuing ligniRcation and suberization of cells, and cell death, seal o_ infections or injuries at the immediate site of cellular penetration and, secondly, if this defence should fail and the stress persist, these same processes promote the prolonged build-up of IAA and ethylene that cause a further metabolic cascade in outlying cells that includes secondary metabolism and growth responses to produce a peridermal defence in depth. A relationship between the strategic location of these phenolic-storing cells within plant tissues and the defence sequence that ensues is proposed
Keywords: CALLOSE; AVANOIDS; HYPERSENSITIVE REACTION; LIGNIFICATION; PERIDERM; PHENOLIC COMPOUNDS; PLANT DEFENCE; PROGRAMMED CELL DEATH; SUBERIZATION; TYLOSES; BANANA (MUSA ACUMINATA L.); CASTOR BEAN (RICINUS COMMUNIS L.); COTTON (GOSSYPIUM HIRSUTUM L.); HOPS (HUMULUS LUPULUS L.); MELON (CUCUMIS MELO L.); PEA (PISUM SATIVUM L.); PEA (PISUM SATIVUM L.); RADISH (RAPHANUS SATIVUS L.); TOMATO (LYCOPERSICON ESCULENTUM MILL.); FUSARIUM OXYSPORUM SCHLECT. F. SPP. SNYD. ET HANS; RALSTONIA SOLANACEARUM E. F. SMITH; SACCHAROMYCES CEREVISIAE VAN DER WALT; VERTICILLIUM ALBO-ATRIUM REINE & BERTH